Broker-based service-oriented content adaptation framework - Md Fudzee, Mohd Farhan (2011)
Electronic documents are becoming increasingly rich in content and varied in format and structure. At the same time, user preferences vary towards the contents and their devices are getting increasingly varied in capabilities. This mismatch between rich contents and user preferences along with the end device capability presents a challenge in providing ubiquitous access to these contents. Content adaptation is primarily used to bridge the mismatch by providing users with contents that is tailored to the given contexts e.g., device capability, preferences, or network bandwidth. Existing content adaptation systems employing these approaches such as client-side, server-side or proxy-side adaptation, operate in isolation, often encounter limited adaptation functionality, get overload if too many concurrent users and open to single point of failure, thus limiting the scope and scale of their services. To move beyond these shortcomings, this thesis establishes the basis for developing content adaptation solutions that are efficient and scalable. It presents a framework to enable content adaptation to be consumed as Web services provided by third-party service providers, which is termed as “service-oriented content adaptation”. Towards this perspective, this thesis addresses five key issues – how to enable content adaptation as services (serviceoriented framework); how to locate services in the network (service discovery protocol);